2010
DOI: 10.1002/lary.20776
|View full text |Cite
|
Sign up to set email alerts
|

Transplantation of bone marrow‐derived neurospheres into guinea pig cochlea

Abstract: The present findings indicate that BMSC-derived spheres can be a source for replacement of spiral ganglion neurons, although further manipulations are required for functional recovery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
2

Year Published

2011
2011
2015
2015

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 14 publications
0
7
0
2
Order By: Relevance
“…The enhanced survival of BMSCs was confirmed in deafened cochleae [26]. Autologous BMSC-derived neurospheres transplanted into the cochlear modiolus of the deafened guinea pigs settled predominantly in the internal acoustic meatus [28]. Combined with those findings, BMSCs can be a source for replacement of SGNs.…”
Section: Regeneration Of Spiral Ganglion Neuronsmentioning
confidence: 72%
See 2 more Smart Citations
“…The enhanced survival of BMSCs was confirmed in deafened cochleae [26]. Autologous BMSC-derived neurospheres transplanted into the cochlear modiolus of the deafened guinea pigs settled predominantly in the internal acoustic meatus [28]. Combined with those findings, BMSCs can be a source for replacement of SGNs.…”
Section: Regeneration Of Spiral Ganglion Neuronsmentioning
confidence: 72%
“…We review previous reports and discuss obstacles to overcome for successful functional recovery. Several kinds of pluripotent stem cells have been delivered into the cochlea for the regeneration of SGNs, including NSCs [10,13,46], ESCs [4,5,11,12,29,34,36,38], bone marrow stem cells (BMSCs) [26,28,40], and iPSCs [27]. Tamura et al, evaluated the ability of NSCs to achieve neural differentiation in the modiolus of the cochlea and demonstrated that some grafted NSCs expressed β-III tubulin, a neuronal marker, although the majority of them differentiated into glial cells [46].…”
Section: Regeneration Of Spiral Ganglion Neuronsmentioning
confidence: 99%
See 1 more Smart Citation
“…Em contrapartida, a cóclea é considerada um sítio imunologicamente privilegiado, pois apresenta uma imunoproteção natural, a barreira hematolabiríntica (Hildebrand et al, 2005). Por este motivo, não houve qualquer reação inflamatória tecidual compatível com reação enxertohospedeiro nos trabalhos em que foram usados xenotransplantes (Cho et al, 2011;Pandit et al, 2011;Ogita et al, 2010;Hu et al, 2009;Lang et al, 2008;Matsuoka et al, 2007;Coleman et al, 2006;Hildebrand et al, 2005). Carlsbad, CA, USA).…”
Section: Razão Para a Escolha Do Xenotransplanteunclassified
“…Atualmente o transplante de CT para o tratamento da surdez é considerado um tratamento promissor. Nos últimos anos, as CT mais utilizadas experimentalmente para este fim são as de medula óssea (Ogita et al, 2010), neurais (Parker et al, 2007) e embrionárias (Corrales et al, 2006).…”
Section: Eficiência Da Neomicina Como Indutor De Perdaunclassified